2004
DOI: 10.1128/mcb.24.16.6957-6966.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of the Maintenance of Peripheral T-Cell Anergy by TAB1-Mediated p38α Activation

Abstract: In anergic T cells, T-cell receptor (TCR)-These results imply that TAB1-mediated activation of p38␣ in anergic T cells regulates the maintenance of T-cell unresponsiveness both by inhibiting IL-2 production and by promoting IL-10 production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…1 T cells is dominant and a target for inhibition of both IL-10 production and unresponsiveness [14]. In the present study we found that depletion of CD25 1 Treg in combination with treatment with a p38 chemical inhibitor (p38-inhibitor) is necessary to completely block the immunosuppressive function of IL-10-producing anergic CD25 À iTreg, which suggested that a combination of treatment by both methods may be important to the success of peptide immunotherapy in cancer patients.…”
Section: Anergic Cd4mentioning
confidence: 56%
See 1 more Smart Citation
“…1 T cells is dominant and a target for inhibition of both IL-10 production and unresponsiveness [14]. In the present study we found that depletion of CD25 1 Treg in combination with treatment with a p38 chemical inhibitor (p38-inhibitor) is necessary to completely block the immunosuppressive function of IL-10-producing anergic CD25 À iTreg, which suggested that a combination of treatment by both methods may be important to the success of peptide immunotherapy in cancer patients.…”
Section: Anergic Cd4mentioning
confidence: 56%
“…However, the suppressor function that is not mediated by IL-10 in the human iTreg may be distinguished to that of in vivo Ag-induced mouse iTreg. We now suspect that the dominant p38 activation in response to other MAPK (ERK and JNK) in in vivo Ag-induced iTreg is related to both the suppressor function via IL-10 production and the anergic state via cell cycle arrest and p27 expression and not via IL-10 [14]. Recent studies have indicated that p38 activation is required for TGF-b-induced in vitro conversion to iTreg [23,24] and is involved in IL-10 production via innate TLR2 signaling of HSP60 in iTreg [25] or in the induction to iTreg through tDC treated with CpG [26].…”
Section: Il-10-producing Cd25mentioning
confidence: 99%
“…33 p38 MAPK activation by IL-24 and other factors, such as TGF-b, 34 may also contribute to anergy in CLL similarly to that demonstrated in T cells. 35 Since Mda-7 promoted cell survival, it could be expected that its expression level correlates with the clinical/biological status in CLL, and a quantitative study of Mda-7 and phospho-p38 MAPK should be carried out, although in preliminary studies we failed to observe a difference between Ig-mutated vs unmutated patients. The same question should be addressed for CD5.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is an indication that TAB1-dependent p38 phosphorylation occurs in LPS, TNF, and CpG treated B cell lines, a study using MKK3/6 knockout MEF cells showed that TNFinduced p38 activation is solely dependent on MKKs [29]. While the biological contexts of MKK-independent p38 activation still need further investigation, there is a couple of recent publications that support the role TAB-dependent p38 activation under physiological conditions [30][31][32]. This suggests that the activation mechanisms of p38 may vary in different cells under various physiological or pathological conditions.…”
Section: Upstream Kinases That Activate P38mentioning
confidence: 99%